Hyper-CVAD and sequential blinatumomab for newly diagnosed Philadelphia chromosome-negative B-cell acute lymphocytic leukaemia: a single-arm, single-centre, phase 2 trial. Issue 12 (December 2022) - Jabbour, Elias; Short, Nicholas J; Jain, Nitin; Thompson, Philip A; Kadia, Tapan M; Ferrajoli, Alessandra; Huang, Xuelin; Yilmaz, Musa; Alvarado, Yesid; Patel, Keyur P; Garcia-Manero, Guillermo; Macaron, Walid; et al.
Summary: Background: Blinatumomab is effective in relapsed or refractory B-cell acute lymphocytic leukaemia and results in high rates of minimal residual disease negativity. We aimed to establish whether the incorporation of blinatumomab into front-line therapy for acute lymphocytic leukaemia could improve outcomes. Methods: We conducted a single-arm, phase 2 trial at The University of Texas MD Anderson Cancer Center (Houston, TX, USA). Patients aged 14 years or older with confirmed, newly diagnosed Philadelphia chromosome (Ph)-negative B-cell acute lymphocytic leukaemia were eligible, including patients who had received up to one course of chemotherapy before enrolment. Patients received four cycles of intensive chemotherapy (hyper-CVAD [hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone] alternating with high-dose methotrexate and cytarabine), followed by four cycles of blinatumomab consolidation (up to 28 μg/day by continuous intravenous infusion for 28 days, given every 42 days). Maintenance consisted of 15 cycles of alternating blocks of three cycles of POMP (6-mercaptopurine, vincristine, methotrexate, and prednisone) chemotherapy and one of blinatumomab. The primary endpoint was relapse-free survival evaluated in the intention-to-treat population. The trial is registered with ClinicalTrials.gov, NCT02877303, and is still enrolling patients. Findings: Between Nov 14, 2016, and Aug 27, 2020, 38 patients with newly diagnosed B-cell acute lymphocytic leukaemia were treated (median age 37 years [IQR 29–45]; 26 [68%] male; 21 [55%] White, non-Hispanic). With a median follow-up of 37 months (IQR 28–49), estimated 3-year relapse-free survival was 73% (95% CI 56–85). No patients relapsed more than 2 years after the start of therapy. One (3%) patient developed transient grade 3 cytokine release syndrome, and four (11%) patients had a grade 3 blinatumomab-related neurological event. The most common non-haematological grade 3–4 adverse events were infections, which occurred in 14 (37%) of 38 patients during induction and in 27 (71%) of 38 patients during consolidation chemotherapy cycles. One (3%) patient discontinued therapy because of treatment-related neurotoxicity. There were two deaths—one due to infection and one due to respiratory failure—which were not considered treatment-related. Interpretation: Front-line sequential chemotherapy with blinatumomab resulted in encouraging long-term survival. Future randomised studies should evaluate the routine incorporation of blinatumomab in the treatment of patients with Ph-negative B-cell acute lymphocytic leukaemia. Funding: Amgen.